A critical review on the influence of process parameters in catalytic co-gasification: Current performance and challenges for a future prospectus - Shahbaz, M. (Elsevier Ltd, 2020)
Gasification has emerged as a prominent technique to convert biomass, coal, plastic, and municipals wastes sludge (generated from agriculture, industrial, and domestics, urban centers) into energy in the form of gaseous products. However, co-gasification of these materials has many advantages, such as desired product yield and uninterrupted feedstock supply as well as the sustainable utilization and disposal of these wastes. Numerous reviews have been documented based on the gasification of individual materials of biomass and coal, nevertheless, very few reviews have been reported on the process of co-gasification. In co-gasification, the effect of parameters becomes very important when dealing with the co-gasification of different mixed materials. The objective of this review to study the effect of temperature, blending ratio, and equivalence ratio (ER) on catalytic co-gasification of biomass-coal, biomass-plastic, biomass-sewage sludge, and mixed plastic blends. In addition, the effects of these parameters on gaseous products, heating values, tar formation, and gasification performance have been analyzed. It is also important to specify the ranges of parameters for the feed combinations in catalytic co-gasification that will provide a guideline for researchers and commercial enterprises to investigate co-gasification. For temperature from 650 to 750 Â°C found good for hydrogen rich syngas production. Whereas, the ratio of biomass 50 or above and ER of 0.20 and 0.25 were found good for higher hydrogen and lower CO2 and tar production. Moreover, the current issues are related to technology, operational problems, policy requirements and route map for commercial success of co-gasification technology have been highlighted. Â© 2020